THE EFFECT OF PERSONALIZED RECOMMENDATIONS AND ONLINE CUSTOMER REVIEWS ON PURCHASE DECISIONS OF AEROSTREET FOOTWEAR ON THE SHOPEE MARKETPLACE - Syalsa Shabilla; Adi Utama; Muhamad Hidayat (Asosiasi Dosen Muda Indonesia, 2026)
The rise of e-commerce in Indonesia has changed how consumers make decisions about what to buy online. Aerostreet footwear purchases are influenced by Shopee's use of online user evaluations and tailored recommendations. The purpose of this study is to partially and concurrently examine the circumstances and impacts of both factors on purchasing decisions. Purposive sampling was used to pick 100 respondents for the quantitative, descriptive, and verificative procedures. Path analysis and MSI were used to analyze the data. Purchase decisions fall into the fairly excellent group, whereas personalized recommendations and online customer reviews fall into the good category, according to descriptive data. Personalized recommendations (path coefficient = 0.298; t = 3.273; contribution = 11.1%) and online customer reviews (path coefficient = 0.327; t = 3.594; contribution = 13%) have a beneficial impact on purchasing decisions, according to verifiable results. Purchase decisions are strongly influenced by both variables at the same time (F = 15.390; total contribution = 24.1%), with other factors accounting for the remaining 75.9%.